LEGAL RESPONSIBILITY MODEL FOR STATE-OWNED ENTERPRISES (SOE) IN CRIMINAL ACTS OF CORRUPTION - Rosa Darman; Elisatris Gultom (RADJA PUBLIKA, 2025)
Problems in the application of legal accountability to State-Owned Enterprises (SOE) involved in corruption, with a focus on the non-uniformity of the definition of state finance, the application of sanctions, and disparities in the recovery of state losses. The method used in this study is normative research with a descriptive analytical approach, which examines existing laws and regulations and analyzes legal practices applied to SOE involved in corruption. The results of the study indicate that the non-uniformity in the definition of state finance causes difficulties in determining the amount of state losses, while the application of inappropriate sanctions, such as fines, is ineffective in recovering state losses. In addition, there is disparity in criminalization, which has an impact on injustice in the process of recovering state losses, with the Prosecutor's Office being more successful in recovering losses than the CEC. This study recommends standardizing legal definitions, applying more appropriate sanctions such as termination of operations or restructuring of management, and implementing an asset recovery mechanism to increase the effectiveness of recovering state losses